COLLEGE GIRL STUDENTS’ ACADEMIC STRESS AND MENTAL HEALTH IN CONNECTION TO FAMILY ENVIRONMENT - Singh, Rajinder; Saikia, Bismita; Sharma, Pratiksha Kashyap (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This study looks at the relationship between family environment and the mental health and academic stress experienced by college-age girls. Ninety undergraduate students from the Golaghat district of Assam were selected for the current study using a random sampling technique. The present study utilised three different measures to assess academic stress: the Sinha, Sharma, and Mahendra (2001) scale; the Mental Health Battery (Arun Kumar Singh and Alpna Sen Gupta, 1983); and the Family Environment scale (Harpreet Bhatia and N.K. Chadha, 1974). The findings indicated that there was no discernible difference in the academic stress levels of college-age females from rural and urban areas. It shown that college females from rural and urban areas did not significantly differ in terms of their mental health. College girl students’ family environments do not differ significantly based on their location. College female students’ family environments and academic stress are related. Finally, research indicates that the family environment and mental health of college girl students are not significantly correlated.